2016
DOI: 10.1073/pnas.1618657114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 138 pathogenic mutations in presenilin-1 on the in vitro production of Aβ42 and Aβ40 peptides by γ-secretase

Abstract: A hallmark of Alzheimer's disease (AD) is the aggregation of β-amyloid peptides (Aβ) into amyloid plaques in patient brain. Cleavage of amyloid precursor protein (APP) by the intramembrane protease γ-secretase produces Aβ of varying lengths, of which longer peptides such as Aβ42 are thought to be more harmful. Increased ratios of longer Aβs over shorter ones, exemplified by the ratio of Aβ42 over Aβ40, may lead to formation of amyloid plaques and consequent development of AD. In this study, we analyzed 138 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
340
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(372 citation statements)
references
References 67 publications
28
340
3
1
Order By: Relevance
“…Recently, the effect of PS1 familial Alzheimer's disease (FAD) mutations on highly purified γ-secretase activity was reported (23). Interestingly, many mutations, which have been shown to increase the amount of Aβ peptides in vivo, were shown to decrease γ-secretase activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effect of PS1 familial Alzheimer's disease (FAD) mutations on highly purified γ-secretase activity was reported (23). Interestingly, many mutations, which have been shown to increase the amount of Aβ peptides in vivo, were shown to decrease γ-secretase activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…There is not a high degree of spatial correlation between the presence of amyloid plaques and neurodegeneration, also neurodegeneration is not observed in certain patients with significant amyloid plaque burden and significant amyloid plaques have not been found in some patients suffering from AD (Morris et al, 2014). A recent study also showed that 90% of 138 presenilin mutation that are associated with EOFAD showed reduced production of Aβ40 and Aβ42 (Sun et al, 2017), casting some doubt on the amyloid hypothesis in AD. Given the evident failure of any drug therapy targeting amyloid peptides, there is a pressing need to explore alternate hypotheses of AD pathogenesis as a means to develop a successful therapeutic intervention.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Indeed, a recent study employed a knockin approach to investigate the effects two EOFAD PSEN1 mutations have on γ-secretase function and found that these mutations abolished γ-secretase activity (Xia et al, 2015). Correspondingly, another recent study investigated 138 distinct EOFAD PSEN1 mutations and found that 90% of these mutants decreased Aβ production (Sun et al, 2017). Yet 10% of these mutations showed normal or elevated Aβ production.…”
Section: Presenilin and γ-Secretase Functionmentioning
confidence: 99%
“…Recently, Sun et al [105] studied the activity of γ-secretase they had reconstituted in liposomes with PS1 with 138 different mutations, one by one, many of which cause Alzheimer at different age. They could not find any correlation between the amount of Aβ peptides produced, or the Aβ42/40 ratio, and the age of Alzheimer onset.…”
Section: Prevention Is the Only Curementioning
confidence: 99%